Predicting the Performance Impact of Increasing Memory Bandwidth for Scientific Workflows - Gonzalez, Nelson Mimura; Brunheroto, Jose; Artico, Fausto; Park, Yoonho; Carvalho, Tereza; Miers, Charles Christian; Pillon, Mauricio Aronne; Koslovski, Guilherme Piegas (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
The disparity between the bandwidth provided by modern processors and by the main memory led to the issue known as memory wall, in which application performance becomes completely bound by memory speed. Newer technologies are trying to increase memory bandwidth to address this issue, but the fact is that the effects of increasing bandwidth to application performance still lack exploration. This paper investigates these effects for scientific workflows focusing on the definition of a performance model and on the execution of experiments to validate the rationale for the model. The main contribution is based on two observations: memory bound applications benefit more from an increase to memory bandwidth, and the effects of improving bandwidth for a particular application gradually diminish as bandwidth is increased.